STUDY OF ZnO and V2O5 NANOPARTICLES AS HETEROGENEOUS PHOTOCATALYSTS IN DEGRADING ORGANIC POLLUTANTS (ASEAN Engineering Journal, 2013)
Heterogeneous photocatalysis particularly using semiconductor material to degrade organic compound is intensively studied in recent years. Semiconductors are good photocatalysts attributed to theirs light absorption properties, carrier charge transport characteristics and excited-state lifetimes. In this work, mixture of ZnO (3.23 eV) and V2O5 (2.38 eV) nanoparticles were used to degrade RhB solution under UV and visible light irradiation, respectively. The rod-like ZnO nanoparticles have an average diameter of 244.1 ± 94.5 nm whereas spherical-like V2O5 nanoparticles have an average diameter of 231.9 ±14.0 nm. Under UV light irradiation, pure ZnO nanoparticles have the highest photodegradation efficiency with rate constant of 0.034 ± 0.004 min-1 . This was attributed to its high reducing power of electrons and oxidation power of holes for producing free radicals. On the contrary, pure V2O5 nanoparticles demonstrated the highest photodegradation efficiency with rate constant of 0.013± 0.001 min-1 under visible light irradiation since it has profusion absorption in visible light region. The result provides useful guideline for designing a waste water purifier driven by sunlight for organic pollutants removal based on a mixture of wide bandgap and narrow bandgap semiconductor nanomaterials.